The effects of familiarity, orthographic neighbourhood density, letter-length and graphemic complexity on children's reading accuracy. - Laxon, Veronica; Gallagher, Alison; Masterson, Jackie (British Journal of Psychology, 2002)
Six to seven year-old children, divided into two groups according to reading ability, read items designed to examine the effect of orthographic characteristics on reading accuracy. Two experiments were carried out using familiar words and nonwords as stimuli. The words and nonwords had comparable orthographic structures, and the number of orthographic neighbours was manipulated. Both reader groups participated in Expt 1, which involved three-letter items, but only the more-skilled group participated in Expt 2, which involved four-letter items. The results showed that familiar words were read more accurately than nonwords. In addition, the children were more accurate with the three-letter items than the four-letter items, and neighbourhood density affected only three-letter items. Expt 2 allowed comparisons between simple and complex graphemes. Complex vowels were more difficult than simple, and also posed more problems than common complex consonants. The results are discussed in relation to descriptions of orthographic development outlined in models of reading acquisition. Reprinted by permission of the publisher.